Racial Disparities in Prostate Specific Antigen Screening and Referral to Urology in a Large, Integrated Health Care System: A Retrospective Cohort Study. Issue 2 (1st August 2021) - Lu, Caroline D.; Adeyemi, Oluwaseun; Anderson, William E.; Hetherington, Timothy C.; Slawson, David C.; Tapp, Hazel; Eaton, Tara A.; Burgess, Earle F.; Grigg, Claud M.; Zhu, Jason Z.; Gaston, Kris E.; Riggs, Stephen B.; et al.
Abstract : Purpose: Contemporary trends and racial disparities in prostate cancer screening and referral to urology for prostate cancer risk are not well characterized, despite consensus that Black men are at higher risk for poor prostate cancer outcomes. The objective of this study was to characterize current racial disparities in prostate cancer screening and referral from primary care to urology for prostate cancer concern within our large, integrated health care system. Materials and Methods: This retrospective cohort study used data from Atrium Health's enterprise data warehouse, which includes patient information from more than 900 care locations across North Carolina, South Carolina and Georgia. We included all men seen in the ambulatory or outpatient setting between 2014 and 2019 who were ≥40 years old. Clinical and demographic data were collected for all men, including age and race. Racial outcomes were reported for all groups with >2% representation in the population. Between-group comparisons were determined using chi-squared analysis, Wilcoxon rank sum testing and multivariable logistic regression, with significance defined as p <0.05. Results: We observed a significant decrease in prostate specific antigen testing across all age and racial groups in a cohort of 606, 985 men at Atrium Health, including 87, 189 Black men, with an overall relative decline of 56%. As compared to White men, Black men were more likely to undergo prostate specific antigen testing (adjusted OR 1.24, 95% CI 1.22–1.26) and be referred to urology for prostate cancer (adjusted OR 1.94, 95% CI 1.75–2.16). Conclusions: There was a continued significant decline in prostate cancer screening between 2014 and 2019. Despite having modestly elevated odds of being screened for prostate cancer compared to White men, Black men are relatively underscreened when considering that those who undergo prostate specific antigen screening are more likely to be referred by primary care to urology for additional prostate cancer diagnostic evaluation.